Engineering vanadium phosphide by iron doping as bifunctional electrocatalyst for overall water splitting. (10th February 2020) - Suo, Na; Han, Xinqi; Chen, Cheng; He, Xingquan; Dou, Zhiyu; Lin, Zihan; Cui, Lili; Xiang, Jinbao
Abstract: To develop efficiently bifunctional electrocatalysts for oxygen evolution reduction (OER) and hydrogen evolution reaction (HER) favors in the large-scale development of water splitting. Herein, for the first time, Fe doped vanadium phosphide functionalized porous carbon loading on nickel foam (Fex Vy -PC/NF) catalyst is designed from the bimetallic Fe/V metal-organic framework (Fex Vy -MOF) by a combination of solvothermal and phosphorization approach. Interestingly, it is noted that the foreign Fe is introduced to the vanadium phosphide crystal rather than forming two crystals. Thus, the morphology, electron state of vanadium, conductivity and facet exposure of vanadium phosphide are observed to be tuned through adjusting the ratio of Fe to V. Remarkably, the optimized electrocatalyst can deliver 10 mA cm −2 at low overpotentials of 66, 201 mV for HER and OER in 1.0 M KOH. As for the overall water splitting, it only needs a lower potential of 1.56 V to reach 10 mA cm −2 and displays desirable durability attributed to the electron interaction between Fe and V, the good conductivity, porous feature of mother MOF and the graphitic layer encasing the metal nanoparticles. Graphical abstract: A novel advanced iron-tuning vanadium phosphide functionalized carbon material with desirable performance for overall water splitting is constructed. Image 1 Highlights: Fe-doped vanadium phosphide (V2 P) is firstly fabricated derived from Fex Vy -MOF. The shapes, crystal facet and the conductivity of V2 P are tuned by implanting Fe. The higher valence state of V in V2 P is detected by introducing foreign Fe. The optimized Fe1 V3 -PC/NF presents desired HER and OER performance.